PENERAPAN INHALASI SEDERHANA MENGGUNAKAN AROMATERAPI DAUN MINT(MENTHA PIPERITA) TERHADAP PENURUNAN RESPIRATORY RATE DAN PENINGKATAN SPO2 PADA PASIEN TB PARU DI RUANGAN WIJAYA KUSUMA RSUD. OTTO ISKANDAR DINATA TAHUN 2024 - Dwiana Fadillah, Syakilla Dwiana Fadillah (JURNAL KESEHATAN KARTIKA, 2024)
Background: Tuberculosis or TB is a disease caused by infection with mycobacterium tuberculosis, an acid-resistant bacteria (BTA) that occurs in the lungs.  The bacteria attack the lungs which can cause respiratory problems such as chronic cough and shortness of breath.  One way that can be used to reduce shortness of breath in pulmonary TB patients non-medically is the administration of mint leaf aromatherapy (mentha piperita) with simple inhalation or vaporization methods. Objective: The purpose of providing simple inhalation using mint leaf aromatherapy (mentha piperita) to overcome the nursing problem of ineffective airway clearance in patients with pulmonary TB. Methods: The method in this study used a descriptive method with a case report approach in patients with pulmonary TB. Therapy was carried out for 3 days with a frequency of 1 time a day, simple inhalation therapy using mint leaf aromatherapy (mentha piperita) was carried out for 10 minutes, before and after therapy, Respiratory Rate and SpO2 were checked to find out if there were any changes. Results: after giving simple inhalation using mint leaf aroma therapy for 3 days with a frequency of 1 day once experienced a decrease in shortness of breath characterized by improved Respiratory Rate and SpO2 results. Conclusion: Simple inhalation using mint leaf aromatherapy (mentha piperita) performed on Mrs. E is proven to improve airway clearance due to sputum accumulation and shortness of breath. This is evidenced by a decrease in the client's shortness of breath scale which on the first day of simple inhalation administration was on a scale of 4 (0-10) and at the end (day 3) of simple inhalation administration, the client's shortness of breath scale was on a scale of 1 (0-10).